DEVELOPMENT OF SUSTAINABLE HALAL TOURISM: REINTERPRETATION OF THE CRESCENTRATING MODEL BASED ON ECOTHEOLOGY - Chaidar Natsir, Muhammad; Aisyah, Sitti; Zainuddin, Anwar; Nursyams, Nursyams; Salmita, Dewi; Rasman, Rasman; Wahyuni MD, Umi; Syarif Nurdin, Muhammad (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The poor quality of services, both in terms of facilities and religious harmony, remains a significant obstacle to the development of halal tourism destinations. In addition, the discourse on halal tourism has so far focused predominantly on the normative aspects of halal, while the environmental sustainability dimension has not yet received full attention. This study aims to analyze the development of halal tourism in the village of Talole by reinterpreting the crescentrating model based on eco-theology. The method used is qualitative with Miles and Huberman analysis. The results of the study show that Tolole has excellent potential as a halal tourist destination, supported by transportation access, digital promotion, community involvement, and the provision of halal food. However, from an eco-theological perspective, there are weaknesses in the form of anthropocentric bias in accessibility, pragmatic communication, ceremonial environmental practices, and partial services due to limited worship and sanitation facilities. Furthermore, the conventional GMTI crescent model has not addressed the challenges of ecological sustainability. Therefore, reinterpreting the crescent model as ACES-E (accessibility, communication, environment, service–ecotheology) shifts the paradigm of halal tourism from Muslim-friendly to Muslim-responsible, emphasizing both ritual and ecological piety